PELANGGARAN MELAWAN ARAH ARUS LALU LINTAS PADA REMAJA PENGENDARA SEPEDA MOTOR DI DAERAH KHUSUS IBUKOTA JAKARTA:ANALISIS DISONANSI KOGNITIF - Albertus Wahyurudhanto; Ilham Prisgunanto (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2018)
One effort to prevent traffic accidents is to look at the character of road users in the tendency to interpret traffic rules. This study aims to see the influence between experience, decision making and self-justification of the attitude of violation against the flow of traffic in adolescents of high school students in the Capital Special Region of Jakarta. This study used a theoretical study of cognitive dissonance. The conclusion obtained is that the dominant factor in cognitive dissonance is more on the element of behavior change, self experience and the attitude of the decision to commit a violation against the flow of traffic. In contrast to the cognitive dissonance of trust and self-justification, it has a negative effect on the contribution of violating behavior to adolescents in driving. Recommendations that can be used as references by Traffic Police in changing violation behavior against traffic flow in adolescents, by using intimate central parties with them, such as close friends, parents and teachers in their daily interactions. Salah satu upaya pencegahan kecelakaan lalu lintas adalah dengan melihat karakter pengguna jalan dalam kecenderungan memaknai peraturan lalu lintas. Penelitian ini bertujuan melihat pengaruh antara pengalaman, keputusan melakukan, dan pembenaran diri terhadap sikap melanggar melawan arus lalu lintas pada remaja pelajar SMA di Daerah Khusus Ibukota Jakarta. Penelitian ini menggunakan kajian teoritik disonansi kognitif. Kesimpulan yang diperoleh adalah bahwa faktor dominan pada dissonansi kognitif lebih pada unsur perubahan perilaku, pengalaman diri, dan sikap keputusan melakukan pelanggaran melawan arus lalu lintas. Berbeda dengan itu, pada dissonansi kognitif kepercayaan dan pembenaran diri justru berpengaruh terbalik atau negatif dalam kontribusi dengan perilaku pelanggaran pada remaja dalam berkendara. Rekomendasi yang dapat dijadikan referensi oleh Polisi Lalulintas dalam mengubah perilaku pelanggaran melawan arus lalu lintas pada remaja, dengan menggunakan pihak-pihak sentral yang intim dengan mereka, seperti kawan akrab, orang tua, dan guru dalam interaksi mereka sehari-hari.